A Case of New Familiar Genetic Variant of Autosomal Dominant Polycystic Kidney Disease-2: A Case Study - Litvinchuk, Tetiana; Tao, Yunxia; Singh, Ruchi; Vasylyeva, Tetyana L. (Frontiers in Pediatrics, 2015)
Abstract Background: Autosomal dominant polycystic kidney disease (ADPKD) is an autosomal dominant renal cyst disorder due to mutations in genes coding for polycystin1 [PKD1 (85%-90% of cases), on ch 16p13.3] and polycystin 2 [PKD2 (10%-15% of cases), on ch 4q13-23], and PKD3 gene (gene unmapped). It is also associated with TSC2/PKD1 contiguous gene syndrome. ADPKD is usually inherited but new mutations without a family history occur in approximately 10% of the cases. Case presentation: A 17 y.o. boy was followed since he was a 13 y.o. for bilateral cystic kidney disease, hypertension and obesity. The diagnosis was an accidental finding during abdominal CT at age 13 to rule out appendicitis. Performed a renal ultrasonogram also demonstrated a multiple bilateral cysts. Because of parental history of bilateral renal cysts, PKD1 and PKD2, genetic testing was ordered. Results showed, PKD2 variant 1:3 bp deletion of TGT; nucleotide position: 1602_1604; codon position: 512-513; mRNA reading frame maintained. The same mutation later was identified in father. Conclusion: A smaller number of patients have a defect in the PKD2 locus on chromosome 4 (resulting in PKD2 disease). There are not known published cases on this familiar genetic variant of ADPKD2 cystic kidney disease. In this